The Effect of Topical Sucralfate Suspension on Oral Aphthae - Z. Delavarian; H. Orafai; L. Molashahi; A. Pakfetrat (Tehran University of Medical Sciences, 2007)
Objectives: The purpose of this study was to determine the efficacy of oral sucralfate suspension (1gr/10ml) in the treatment of recurrent aphthous stomatitis (RAS). Materials and Methods: Fifty-five patients with oral aphthae were included in this randomized, double-blind, placebo-controlled clinical trial conducted in the Department of Oral Medicine, School of Dentistry, Mashhad University of Medical Sciences. In the first part of the study, all subjects were instructed to rinse with a 10% suspension of sucralfate or placebo, 4 times a day for 2 weeks. Clinical examination was performed two times a week. The second part consisted of topical use of sucralfate or placebo 2 times a day for 4 weeks, followed by biweekly inspections for 6 months. The size and number of the ulcers along with pain severity were assessed in the course of the pretreatment and treatment phases. Recurrence was evaluated during the follow up period. Pearson, c2, and Fisher's exact tests were used for statistical analysis. Results: On the fourth day of the study, pain relief was encountered in 59% and 14% of the case and control patients, respectively. Also, 63% of the ulcers in the sucralfate group and 71% in the placebo group showed size-reduction on the first visit. During the first 7 days of treatment, the number of ulcers showed reduction in both groups, which was significantly larger in the case group. Conclusion: A 10% suspension of sucralfate accelerated pain relief in aphthous patients and its use is recommended as an adjunct for the treatment of RAS.